Chapter Assessment of the chemical quality of sediments in the maritime port of Reunion. Concentrations in trace metals and natural geochemical backgrounds. - Droit, Julie (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The analyzes carried out in the marine sediments sampled in the port and coastal areas of Reunion show, for certain metallic trace elements, significant variations in their contents and regular overruns of the regulatory thresholds for the management of dredged sediments. Several studies show that the volcanic nature of Reunion Island is the cause of high concentrations of metals in the soil. The objective of this study is to define, whether the observed exceedances of the management thresholds for dredged sediments are due to the geology of the island or to contributions of anthropogenic origin.